SADBS: sistemas de agendamentos e doações web e mobile de banco de sangue - Monteiro, Jefferson Tadeu (2013)
The development of a solution of location and scheduling appointments in the Blood Banks of Brazil through mobile devices with Android system is the subject of this paper. Currently blood banks face problems related to stocks due to lack of blood donors, this is due to the fact that people often do not have time or don't know the location of a blood bank. Another relevant point is the issue of scheduling, because people often have to call the blood bank to see if there is agenda available, thus overloading the operators that could do other tasks, such as answering more donors in the same space of time. To solve this problem we developed an android application which the donor can easily make the register and schedule appointments directly by the device, it can also know the location of a blood bank by tracing the route , furthermore there is the possibility of the donor know how many donations were made in the in a particular state. Another important point is the part which is responsible for the Web control queries and donation history of the patient, thus ensuring that blood donation is quick efficient and safe for both donor and to the health professional.